Conmoción subterránea. - Murillo-Matamoros, Ismael (2014)
This paper reports an encounter with short story book, Cosecha de Pecadores (1986) by Rima Vallbona. Through this encounter a two-ways voyage is set off and presented to the audience, one is towards y writer Rima Vallbona's stories on its own right and, the second one is towards the subjectivity of the write of this essay . In both cases this performance activates a riot, a revolution, which is, precisely, the action that serves to entitle this essay.